Aufeises of the Indigirka river basin based on recent Landsat satellite images and historical data - Olga Makarieva; Andrey Shikhov; Andrey Ostashov; Nataliia Nesterova (Лëд и снег)
The paper presents the methods and the results of the development of the digital catalogue of aufeises for the Indigirka river basin, with the use of Landsat images and historical data. The studied basin of the Indigirka river to the Vorontsovo gauging station has an area of 305000 km2. Historical data origins from the Cadastre of naleds of the North-East of the USSR published in 1958 and topographic maps. It includes the estimated coordinates and characteristics of 897 aufeises with total area of 2064 km2. The Landsat-based identification of aufeises for 2013-2017 allowed the description of 1213 aufeises on a total area of 1287 km2. The combined digital catalogue of the aufeises for Indigirka river basin based on the union of two sources is available at https://issues.pangaea.de/browse/PDI-17699.10% of the largest aufeises make up about 60% of the total area of all aufeises according to both sources. The largest number of aufeises is observed at altitudes of 900-1300 m.The interannual variability of the aufeises area was estimated by the example of the Bolshaya Momskaya naled and the group of large aufeises in the basin of the Syuryukty River for the period of 2001-2016. The conclusions cannot be considered unambiguous due to the limitations of the imagery data but the results of analysis indicate a tendency towards a decrease in the area of the the Bolshaya Momskaya naled in recent years and the reduction in the aufeises area in the basin of the Syuryukty River has not occurred.The main results of the study are the new geodatabase of the aufeises of Indigirka river basin, and also the comparison of satellite observations with historical data. It is shown, that the satellite-estimated total area of aufeises is 1,6 times less than in the Cadastre (1958). At the same time, it was found more than 600 aufeises by Landsat images analyses which are missing in the Cadastre (1958). Thus, the Cadastre (1958) data are incomplete. On the other hand, the aufeises formation conditions may have been significantly changed between the mid-20th century and the present.